EKSEKUSI OBJEK JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN DAN AKIBAT HUKUMNYA BAGI KREDITUR (Studi Pada BRI Cabang Takengon dan PT. Mandala finance Cabang Takengon) - YANTI ARNILIS (Ilmu Hukum Prima (IHP), 2021)
The juridical consequence for a creditor who does not register his fiduciary collateral deed is that it is not protected by the Law No. 42/1999 on Fiduciary Collateral. The research problems are how about the legal consequence for a creditor who does not register his fiduciary object, how about the execution of unregistered fiduciary object in Bank BRI Takengon Branch and PT. Mandala Finance, and how about the obstacles encountered and efforts made by Bank BRI Takengon Branch and PT. Mandala Finance in the execution of the unregistered fiduciary object. The legal consequence for a creditor who does not register his fiduciary object is that the fiduciary object does not have any material rights for either Bank or financing companies as the creditor, the creditor does not have preference rights, the creditor does not have the rights to execute the fiduciary object and cannot request for protection to the police. What impedes Bank BRI Takengon Branch from conducting the execution is the provisions regulating that the minimum amount of a fiduciary object is IDR 50,000,000 (fifty million Rupiahs), the execution process takes much time, the fiduciary object is destroyed, the facility receiver name is different, the values of the fiduciary object is declined, and the debtor has different address. The impediment which is not included into a legal category is that the society has little understanding of fiduciary collaterals. The obstacles encountered by PT. Mandala Finance in the execution is that PT. Mandala Finance cannot make an execution because he has not registered the fiduciary object to the Fiduciary Collateral Office. The efforts made by BRI Takengon Branch is making an agreement; the execution is conducted by using an agreement of ownership right transfer of the object with trusts, by filinga simple lawsuit and re-registering the fiduciary object. The efforts that can be made by PT. Mandala Finance in the execution of the unregistered fiduciary object is by issuing Power of Attorney to grant the withdrawal authority and make negotiations with the debtor.